Women and Gender in the Mines: Challenging Masculinity Through History: An Introduction - Romano, Rossana Barragán; Papastefanaki, Leda (International review of social history, 2020)
The role of women as mineworkers and as household workers has been erased. Here, we challenge the masculinity associated with the mines, taking a longer-term and a global labour history perspective. We foreground the importance of women as mineworkers in different parts of the world since the early modern period and analyse the changes introduced in coal mining in the nineteenth and early twentieth century, the masculinization and mechanization, and the growing importance of women in contemporary artisanal and small-scale mining. The effect of protective laws and the exclusion of women from underground tasks was to restrict women's work more to the household, which played a pivotal role in mining communities but is insufficiently recognized. This process of “de-labourization” of women's work was closely connected with the distinction between productive and unproductive labour. This introductory article therefore centres on the important work carried out in the household by women and children. Finally, we present the three articles in this Special Theme and discuss how each of them is in dialogue with the topics addressed here. Many thanks also to Marie-José Spreeuwenberg for her invaluable engagement.